Language Skills Test in Language Teaching Evaluation - Nabila Rahma Mardhotillah; Selly Cahyanti Iskandar; Nur Ikhfan; Yayan Sudrajat (PT. Lancar Media Komunikasi, 2023)
This article contains an overview or explanation of language skills tests, indicators, concrete examples and rubrics contained in evaluating language teaching. Students who are skilled at language are the fruit of successful language learning. Learning can be successful, one of which is due to regular and measurable evaluations. One way to conduct an evaluation is to do a test. The language skill test consists of: listening skill test, speaking skill test, reading skill test, and writing skill test. This article was also created with the aim of helping anyone who reads to understand the definitions, indicators, concrete examples and rubrics of the four language skills tests that can be applied in language learning. This article was prepared using the literature review method, referring to the opinions of experts and relevant studies.